From Poverty Reduction to Poverty Resilience: Koperasi Merah Putih and the Strengthening of Local Economic Resilience in Indonesia - Yusriadi Yusriadi; Muslimin; A. Septian Abdi; Vivi chairunnisa; Usman (Journal of Indonesian Scholars for Social Research, 2026)
Poverty reduction in Indonesia has increasingly moved beyond short-term welfare assistance toward a broader agenda of strengthening local economic resilience. This article examines how Koperasi Merah Putih can be positioned as a strategic local economic institution for supporting poverty resilience in Indonesia. Using a secondary data-based policy analysis, the study explores the relationship between poverty reduction, structural vulnerability, and the role of village-level cooperative institutions in strengthening community economic capacity. The article argues that poverty resilience requires more than declining poverty rates; it depends on the ability of local communities to access productive resources, stabilize household livelihoods, improve market participation, and build collective economic mechanisms that can protect vulnerable groups from future shocks. Koperasi Merah Putih is viewed in this study as a positive institutional innovation that reflects the government’s commitment to strengthening grassroots economic development. Through its potential roles in facilitating access to basic goods, local distribution networks, productive financing, food supply chains, and community-based enterprise development, the cooperative can support a more inclusive and adaptive model of poverty alleviation. The article highlights that the effectiveness of poverty resilience depends on the interaction between local institutional capacity, human development, employment opportunities, digital connectivity, and regional economic structures. By shifting the analytical focus from poverty reduction to poverty resilience, this study contributes to poverty governance literature and offers a policy-relevant framework for understanding how cooperative-based local institutions can strengthen Indonesia’s long-term poverty alleviation agenda.